Chapter 32 Mainland Southeast Asia After Angkor On the Legacies of Jayavarman VII - Thompson, Ashley (Taylor & Francis, 2023)
This chapter will look beyond Cambodia as we know it today in geographic terms, and beyond the early 13th century, to highlight legacies of Angkor beyond Angkor on the Southeast Asian mainland (see Figure 32.1). To begin this exploration, allow me to point out the discreetly deceptive premises of this chapter's title: that we all, author and readers alike, share established understandings of what Angkor was as of what a legacy is. Alas, we cannot pretend to stand on such firm ground. Instead, with reference to the opening epigraphs, I propose a working definition of Angkor as legacy. The conceptual assimilation of 'Angkor' and 'legacy' is of course another temporising gloss on empire: where the present, commemorating what has been as a means of heralding what will be, is always already gaining time for itself.